Application of metal matrix nanocomposites in engineering - Jovana Krstić; Jelena Jovanović1; Sandra Gajević; Slavica Miladinović; Nikolaos Vaxevanidis; Imre Kiss; Blaža Stojanović (Advanced Engineering Letters)
Nanocomposites nowadays, have the tendency to replace conventional composite materials in many commercial products. These composites find application in a diverse range of fields, including computer components, data storage systems, various membranes and filters, as well as advanced materials in the automotive and aerospace industries. They are available in different forms and from various manufacturers, providing a wide selection. Although they may be more expensive, compared to conventional materials, the ability to customize the properties of nanocomposites to the specific needs of end-users makes them highly attractive and innovative. International scientific bodies, including International Standards Organization (ISO), are actively working on formulating standards to regulate the safe use, disposal and recycling of nanowaste. The importance of standardization will grow with the expansion of the market for metal matrix nanocomposites. The aim of this paper is to review the existing research on metal matrix nanocomposites and their application to achieve significant improvements in the chemical, aerospace, automotive and other industries.